Concern and credibility: a factorial survey experiment on nurse judgments and intent to report patient-expressed safety events - Patricia S. Groves; Yelena Perkhounkova; Amany Farag; Maria Hein; Janice A. Sabin; Matthew J. Witry; Brad Wright (BMC Nursing)
Abstract Background Hospitalized patients continue to experience preventable harm and safety threats. The purpose of this study was to evaluate the extent to which nurse judgments of credibility and concern (perceived importance) mediated the relationships between patient demographic characteristics and nurse intent to report a patient-reported safety event while adjusting for nurse and event characteristics. Methods A cross-sectional, quantitative study using a factorial survey experiment was conducted. Hospital nurses working in United States practice settings (N = 240) participated in an online survey. Path analysis was used to test the study model. Results Our findings indicate that increased nurse concern regarding a patient-reported safety event increased the likelihood of reporting the event to organizational incident reporting systems. Nurse concern also mediated the relationship between patient socioeconomic status and race/ethnicity (Black vs. non-Hispanic White) and nurses’ intent to report. Other variables directly affecting intent to report were patient ethnicity (Hispanic White versus Non-Hispanic White), and event type (medication versus miscommunication). The degree of credibility judged by participants had no effect on intent to report. Conclusions These results suggest key motivations for nurse reporting are (a) the degree of concern (perceived importance) of the event and (b) the type of event, with medication errors associated with both greater nurse concern and intent to report. While literature suggests that patient characteristics are directly and indirectly associated with intent to report, our study suggests credibility is not a mitigating factor in that relationship. Overall, our study suggests interventions focusing on nurse judgments of importance may be more effective than those focused on judgments of credibility.